2022
DOI: 10.2196/39085
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of Smartphone Approaches to Assess Physical Activity in Healthy Young People: Systematic Review

Abstract: Background Physical inactivity is a preventable risk factor for several chronic diseases and one of the driving forces behind the growing global burden of disease. Recent evidence has shown that interventions using mobile smartphone apps can promote a significant increase in physical activity (PA) levels. However, the accuracy and reliability of using apps is unknown. Objective The aim of our review was to determine the accuracy and reliability of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Second, the accuracy of the step counts recorded by the app could not be validated. Several previous studies found that step counts recorded by smartphone apps are generally reliable; however, this varies significantly depending on the app used (30)(31)(32). However, this study focused on intraindividual changes in daily step counts, and individual participants probably used the same application throughout the study period.…”
Section: Discussionmentioning
confidence: 96%
“…Second, the accuracy of the step counts recorded by the app could not be validated. Several previous studies found that step counts recorded by smartphone apps are generally reliable; however, this varies significantly depending on the app used (30)(31)(32). However, this study focused on intraindividual changes in daily step counts, and individual participants probably used the same application throughout the study period.…”
Section: Discussionmentioning
confidence: 96%
“…Rezagholi et al [ 29 ]–also allows for the development of cheaper data collection strategies, where the subject herself is responsible for larger parts of the data collection and data are transferred to the researchers only for further processing and analysis, which may even be automated [ 57 ]. In some cases, the subject may even collect and share posture data collected using the in-built accelerometers in her smart phone [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone accelerometers can measure the acceleration acting on the device. This sensor has been used to estimate parameters related to human motion, including number of steps [12,13], gait and balance [14][15][16][17], jump characteristics [18,19], tremor [20], heart rate [21], and breathing pattern [22,23]. Research shows that some of the metrics computed from smartphone accelerometers are valid compared to laboratory equipment and reliable between days [15][16][17]24].…”
Section: Accelerationmentioning
confidence: 99%